The role of hyaluronic acid in PBS/IC treatment – and its benefits for the sexual function - Bartl, Igor; Mišanko, Vladimír; Šetina, Róbert; Caňo, Michael (Abstracts of the 3rd Czech and International Congress of Andrology, 2008)
The pelvic pain treatment is a quite complicated problem with little success in determing its patophysical causes. The permanent or repeated chronic non-malignant pain, accompanied by functional involvement amplified by mental factors, will often end in a sexual dysfunction. Material and methods: Our team of authors from the Department of Urology of the University Hospital Ruzinov in Bratislava is presenting a group of patiens from 2005-2007, who suffered from severe pelvic pain for at least 6 months. The patiens, all with various diagnosises, were treated by using an intracavitary instillation of hyaluronic acid directly into the bladder. Results: After completing this treatment, we evaluated the various changes in CPP (chronic pelvic pain) before and after treatment by means of questionnaires. After the treatment, the patients reported a 64% overall improvement: 45% improvement in bladder control, 31% improvement in pain during or after sexual intercourse, 37% improvement in sexual function satisfaction, and 66% improvement in overall quality of life. Conclusions: Our goal is to present the intracavitary instillation of hyaluronic acid as a safe, well-tolerated, treatment with easy application. Its application can be done in a clinical environment; another significant fact when considering the pharmacoeconomic factor of PBS/IC treatment.